Crack-containing hot stamped coated steel parts with excellent spot weldability and excellent paint adhesion

JP7642164B1Active Publication Date: 2025-03-07ARCELORMITTAL SA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024539310
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-02-09
Publication Date
2025-03-07
Estimated Expiration
2044-02-09

Smart Images

  • Figure 0007642164000001_ABST
    Figure 0007642164000001_ABST
Patent Text Reader

Abstract

In a hot stamped coated steel part including a steel substrate and an aluminum alloy coating including an interdiffusion layer and an outer layer from the steel substrate outward, the total thickness of the coating e coating and the thickness of the interdiffusion layer e IDL satisfies the following conditions: 40≦E pc At ≦80, TIFF0007642164000040.tif13161Hot stamped coated steel parts are 0.6mm~3.5mm thick e Pflat The coating of the non-deformed portion has a linear density of cracks dC, which is defined as the minimum linear density of cracks dCmin(e Pflat )That's all. TIFF0007642164000041.tif10161
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hot stamped coated steel part comprising a steel substrate and an aluminum alloy coating on at least one side of the steel substrate, the coating having an optimized crack density, the part having excellent paint adhesion and excellent spot weldability. The present invention also relates to a method for producing the hot stamped coated steel part. [Background technology]

[0002] Such parts can also be used, for example, in the automotive industry for the manufacture of structural elements for anti-intrusion or energy absorbing functions.

[0003] In this type of application, it is desirable to have steel parts that combine high mechanical strength, high impact resistance, good corrosion resistance and dimensional accuracy. Automotive parts such as front or rear rails, roof rails, B-pillars, and chassis parts such as lower control arms, engine cradles, etc. more specifically require these properties.

[0004] To meet these demands, such parts are now generally manufactured by the hot stamping process (also called press hardening). In the hot stamping process, as disclosed in particular in patents FR 2 780 984 and FR 2 807 447, a blank cut from a steel sheet precoated with a metal or metal alloy is heated in a furnace to a temperature at which the ferrite and cementite microstructure of the low carbon steel is at least partially transformed into austenite and then hot stamped in a die. During stamping, the part is held in the die to achieve rapid cooling, which leads to the formation of the desired hardened microstructure and the acquisition of the desired mechanical properties. The precoating can be aluminum or an aluminum alloy. During heating in the furnace, the precoating alloy alloys with the steel substrate to form compounds that provide protection of the steel surface against decarburization and the formation of scales.

[0005] Recently, there has been a lot of focus on the coating of parts after hot stamping and how it affects the properties of the part in service.

[0006] In WO 2008 / 053273 it was proposed to limit the pre-coating thickness to between 20-33 μm everywhere and to control the hot stamping process, in particular the heating rate and the austenitizing parameters, in order to achieve a favorable continuity and morphology of the continuous layer during the coating of the component, leading to improved weldability. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] French Patent No. 2780984 [Patent Document 2] French Patent No. 2807447 [Patent Document 3] International Publication No. 2008 / 053273 Summary of the Invention [Problem to be solved by the invention]

[0008] However, it remains desirable to provide hot stamped steel parts that can be produced with a wide range of pre-coating thicknesses, and that have improved spot weldability and improved paint adhesion.

[0009] In particular, the inventors have found that even though paint adhesion can be improved, such improvement is achieved at the expense of spot weldability, such that it remains desirable to provide a part that combines good paint adhesion with good spot weldability.

[0010] It is therefore an object of the present invention to provide a hot stamped coated steel part comprising a steel substrate and an aluminium alloy coating on at least one side of the steel substrate, and a method for producing the same, which simultaneously has excellent paint adhesion and excellent spot weldability.

[0011] In particular, it is desirable to provide hot stamped coated steel parts having at least a non-deformed part with a weld range of more than 1 kA measured according to standard SEP 1220-2 (2011) together with excellent paint adhesion. The paint adhesion is evaluated by carrying out a dry paint test and a wet paint adhesion test according to standard ISO 2409:2013. If the result of the dry paint test is strictly less than 1 and the result of the wet paint adhesion test is less than or equal to 1, the paint adhesion is considered to be excellent. [Means for solving the problem]

[0012] For this purpose, the invention relates to a hot stamped coated steel part according to claim 1.

[0013] The hot stamped coated steel part preferably has one or more of the features of claims 2 to 13.

[0014] The invention also relates to a method for producing a hot stamped coated steel part according to claim 14.

[0015] The method preferably comprises one or more of the features of claims 15-24.

[0016] The invention also relates to the use of a hot stamped coated steel part according to the invention or a hot stamped coated steel part produced by the method according to the invention for the production of a chassis or body-in-white part or a suspension arm for an automotive vehicle.

[0017] The invention will now be described in detail and illustrated by examples, without being limited thereto, in view of the following figures. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 shows a schematic diagram of an example of a hot stamped coated steel part according to the present invention. [Diagram 2] 3 is a cross-sectional view of a coating of a non-deformed portion of a part according to the invention, as viewed in a given field of view. [Diagram 3] FIG. 13 shows an example of a cross-section of a coating on a non-deformed portion of a comparative part where no cracks are present. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention relates to hot stamped coated steel parts.

[0020] Hot stamped coated steel parts are non-flat parts produced by hot stamping a blank.

[0021] Steel plate refers to flat steel sheet, either hot-rolled or cold-rolled in coil form or cut from such a coil.

[0022] A steel sheet has a top and a bottom surface, also called the top and bottom sides or top and bottom surfaces. The distance between said surfaces is designated as the thickness of the sheet. The thickness can be measured, for example, using a micrometer, whose spindle and anvil are arranged on the top and bottom surfaces, with the axis between the spindle and the anvil perpendicular to the surface of the sheet. Similarly, the thickness can also be measured on formed parts. Similarly, the thickness can also be measured on blanks and parts.

[0023] A steel blank refers to a flat sheet of steel cut to any shape suitable for its use, or to a blank produced by cutting two or more steel plate materials, which may have different thicknesses or different compositions, to the required shape and assembled together, especially welded together.

[0024] Average thickness of a part or portion of a part means the overall average thickness of the material that makes up the part after it has been initially formed from a flat sheet into a three-dimensional part.

[0025] Uniform thickness means that the thickness of the blank, part, sheet or area or part thereof considered is constant and that the maximum variation in thickness of the blank, part, sheet or area or part thereof above or below the average thickness of the blank, part, sheet or area or part is a maximum of 0.1 mm. In particular, uniform thickness means that no variations in thickness were spontaneously introduced during production, in particular during the production of the sheet in hot and / or cold rolling, as well as during the forming operations of the production of the part.

[0026] In the following, the thickness of a blank, part, sheet, or area or portion thereof having a uniform thickness is defined as the average thickness of this blank, part, sheet, or area or portion thereof.

[0027] Additionally, the term "thickness" is used to refer to the thickness of a blank, part, sheet, or region or portion thereof of uniform thickness, while "average thickness" is used more generally to refer to the average thickness of a blank, part, sheet, or region or portion thereof, whether the thickness is uniform or variable.

[0028] A tailor welded blank is manufactured by assembling together several sheets or cut out blanks of steel, known as sub-blanks, for example by laser welding, to optimize the performance of the part in its different areas, to reduce overall part weight, to reduce overall part cost, and to reduce material scrap. The sub-blanks that form a tailor welded blank can be assembled with or without overlap, for example, they can be laser butt welded (no overlap) or spot welded to each other (with overlap).

[0029] A flexible blank is a type of tailor welded blank that includes areas where at least some of the connections between different sub-blanks are not rigid, allowing the sub-blanks to move in different directions during the forming operation in the corresponding areas.

[0030] In contrast to a tailor welded blank, a monolithic blank refers to a blank that consists of a single sub-blank, without several sub-blanks being joined together.

[0031] A tailor rolled blank is a blank with variable thickness, i.e. a change in thickness along the blank, obtained by differential rolling during the steel sheet manufacturing process.

[0032] Hot stamping is a forming technique that involves heating a blank to a temperature at which the microstructure of the steel is at least partially transformed into austenite, forming the blank at high temperature by stamping the blank, and quenching the formed part to obtain a microstructure with high strength. Hot stamping makes it possible to obtain very high strength parts with complex shapes and presents many technical advantages.

[0033] A monolithic part is a hot stamped part produced from a monolithic blank.

[0034] A monolithic part may be manufactured, for example, from a monolithic blank having a uniform thickness or from a monolithic tailor rolled blank.

[0035] A hot stamped welded steel part or hot stamped laser welded steel part is a hot stamped part produced from a tailor welded blank, e.g. a flexible blank. A hot stamped welded steel part therefore comprises two or more hot stamped sub-parts and one or more hot stamped welds joining the hot stamped sub-parts together.

[0036] In one embodiment, the hot stamped coated steel part of the present invention is a monolithic part.

[0037] In another embodiment, the hot stamped coated steel part is a hot stamped welded steel part.

[0038] The hot stamped coated steel parts of the present invention preferably have an average thickness e comprised between 0.6 mm and 3.5 mm. P has.

[0039] The range of 0.6 mm to 3.5 mm is the usual thickness used for the manufacture of structural or reinforcing parts for the automotive industry. This thickness range is also suitable for industrial press hardening tools, especially hot stamping presses or dies.

[0040] Furthermore, as will be described in more detail below, the thermal process applied to a given steel thickness will affect the formation of cracks in the coating, particularly in the flat, non-deformed portions which are desired in the present invention.

[0041] Preferably, the average thickness e of the hot stamped coated steel part P is in the range of 0.7mm to 3.0mm.

[0042] In one embodiment, the hot stamped coated steel part has a uniform thickness e of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm. P has.

[0043] In another embodiment, the hot stamped coated steel part has a variable thickness (and is therefore non-uniform). In that case, the hot stamped coated steel part has different uniform thicknesses e, preferably between 0.6 mm and 3.5 mm, preferably between 0.7 mm and 3.0 mm, respectively. Pi The gyroscope comprises two or more regions having the following structure:

[0044] As an example, hot stamped coated steel parts with variable thickness can be produced from tailor rolled blanks with variable thickness obtained by differential rolling during the steel plate manufacturing process.

[0045] As another example, a hot stamped coated steel part with variable thickness can be a hot stamped welded steel part produced from a tailor welded blank made from blanks having different thicknesses.

[0046] A hot stamped coated steel part comprises a steel substrate (also called a steel base material) having two major surfaces.

[0047] The steel in the substrate is a steel for hot stamping, i.e. a steel which can be hardened after austenitizing and quenched by quenching.

[0048] In one embodiment, the component is manufactured from a monolithic blank, with the steel substrate being made from a single piece of steel.

[0049] In another embodiment, the part is a hot stamped welded steel part, where the steel substrate consists of two or more regions (or sub-parts) which may be made of the same or different steels and may have the same or different microstructures.

[0050] In the following, by steel microstructure and composition of a steel substrate is meant the microstructure and composition of the steel substrate (if the substrate is made of a single piece of steel) or the microstructure or composition of one or more regions or sub-parts of the steel substrate.

[0051] The composition of the steel depends on the desired mechanical properties of the part. However, preferably, in the steel substrate or in each region of the steel substrate, the steel comprises, in weight percent: 0.062%≦C≦0.4% 0.4%≦Mn≦3.9% 0.10%≦Si≦1.5% 0.005%≦Al≦1.0% 0.001%≦Cr≦2.0% 0.001%≦Ti≦0.2% 0.0005%≦B≦0.010% Ni≦2% Nb≦0.1% Mo≦0.65% W≦0.30% N≦0.010% 0.0001%≦S≦0.05% 0.0001%≦P≦0.1% Ca≦0.005% The remainder of the composition is iron and unavoidable impurities resulting from processing.

[0052] The levels of impurities resulting from the processing process depend on the manufacturing route used. For example, when using the blast furnace route with low levels of steel scrap (recycled steel), the levels of impurities remain very low. On the other hand, when the steel is smelted using an electric furnace with a very high proportion of recycled scrap steel, the levels of impurities increase significantly. In this latter case, for example, the levels of Cu can rise to 0.25%, Ni can rise to 0.25%, Sn can rise to 0.05%, As can rise to 0.03%, Sb can rise to 0.03% and Pb can rise to 0.03%.

[0053] Thus, in one embodiment, the steel contains, as unavoidable impurities, max. 0.25% Cu, max. 0.05% Sn, max. 0.03% As, max. 0.03% Sb and / or max. 0.03% Pb.

[0054] The above composition is advantageous for achieving high mechanical properties, in particular a tensile strength TS in the range of 950 MPa to 2100 MPa.

[0055] The tensile strength is measured according to the ISO standard NF EN ISO 6892-1 published in October 2009. Tensile specimens are cut from a flat section of the hot stamped part.

[0056] In the following, unless otherwise stated, the contents in the elements are expressed as weight percentages.

[0057] The carbon content depends on the desired tensile strength TS of the hot stamped coated steel part.

[0058] Below a C content of 0.062%, it is difficult to obtain a tensile strength of at least 950 MPa after hot stamping under any cooling conditions. Above 0.4%, in combination with other elements of the composition, the adhesion of the coating after hot stamping may not be satisfactory, and the resistance to delayed cracking and toughness of the steel are reduced. In one embodiment, the C content is maximum 0.38%.

[0059] The C content depends on the desired tensile strength TS of the hot stamped part produced by hot stamping the steel sheet. In one embodiment, the C content is 0.062% to 0.095%. If a higher tensile strength is desired, the C content can be increased to a range of 0.15% to 0.30%, at about 1500 MPa. If the tensile strength needs to be further increased to at least 1800 MPa, the C content can be added at a content of up to 0.4%.

[0060] Apart from its deoxidizing role, manganese has an important effect on hardenability, especially if its content is at least 0.4%. Above 3.9%, the stabilization of austenite by Mn can be too important, which can lead to the formation of too pronounced banding. Preferably, the Mn content is maximum 3.0%.

[0061] Silicon is added in a content of at least 0.10% to help deoxidize the molten steel and to contribute to the hardening of the steel by precipitation in solid solution. However, its content is generally limited to avoid excessive formation of silicon oxides, which impair the coatability of the steel. The silicon content is therefore generally not more than 1.5%, for example not more than 0.80%.

[0062] Aluminum may be added as a deoxidizer with a content of at least 0.005%. Furthermore, Al can protect boron by bonding with N when the titanium content is insufficient. The Al content is preferably at least 0.01%. To avoid oxidation problems and to avoid the formation of ferrite during hot stamping, the Al content is generally not more than 1.0%. Preferably, the Al content is at most 0.1%.

[0063] Cr may be added to increase the hardenability of the steel and contribute to achieving the desired tensile strength after hot stamping. When Cr is added, its content is 0.01% or more, preferably 0.1% or more, up to 2.0%. When no optional addition of Cr is made, the Cr content may be present as an impurity at a content as low as 0.001%.

[0064] If titanium is added, its content is preferably at least 0.008% and at most 0.2%. If the Ti content is comprised between 0.008% and 0.2%, precipitation at very high temperatures occurs in the form of TiN, and then at lower temperatures in the austenite in the form of fine TiC, resulting in hardening. Furthermore, if titanium is added in addition to boron, titanium prevents the combination of boron with nitrogen, and nitrogen combines with titanium. Therefore, the titanium content is preferably 3.42 * N is higher than N, where N is the N content by weight percent in the composition. However, the Ti content should preferably remain below 0.2%, preferably below 0.1%, more preferably max 0.05% to avoid the precipitation of coarse TiN precipitates. If no optional addition of Ti is made, Ti is present as an impurity with a content of at least 0.001%.

[0065] Boron is added in a content of at least 0.0005% and at most 0.010% in order to increase the hardenability of the steel. Preferably, the B content is at most 0.004%.

[0066] In one embodiment, Ni can be added in a content of up to 2%, typically at least 0.25%, preferably up to 0.5%, in order to reduce the susceptibility to delayed fracture by concentrating at the surface of the part. If not added, Ni can be present as an impurity in a content as low as 0.001%. Depending on the manufacturing route used, the Ni content as an impurity can be as high as 0.25% (e.g. when producing steel with a high proportion of recycled scrap steel) or as high as 0.1% (e.g. when using lower levels of steel scrap).

[0067] Niobium is sometimes added up to 0.1% to obtain precipitation hardening and microstructure such as austenitic grain size. Nb further improves the ductility of the steel. If Nb is added, its content is preferably at least 0.01%. The Nb content is preferably up to 0.06% to avoid the formation of coarse (Ti,Nb)(C,N) precipitates.

[0068] Molybdenum may be added in a content of up to 0.65%. If Mo is added, its content is preferably at least 0.05%. Mo is preferably added together with Nb and Ti to form co-precipitates that are very stable at high temperatures. Mo may also be added to increase the toughness of the steel, acting as a grain boundary strengthener in solid solution. The optimum effect is obtained when the Mo content is comprised between 0.15% and 0.25%.

[0069] W may be added to increase the hardenability and hardenability of the steel by forming tungsten carbide. If W is added, its content is 0.001% to 0.30%.

[0070] Sulfur, phosphorus and nitrogen are commonly present in steel compositions as impurities.

[0071] The nitrogen content is generally at least 0.0005%. In order to prevent the precipitation of coarse TiN precipitates, the N content is generally at most 0.010%, preferably at most 0.005%.

[0072] In excess, sulfur and phosphorus reduce ductility. Therefore, their contents are limited to 0.05% and 0.1%, respectively.

[0073] In particular, the presence of S in molten steel can lead to the formation of MnS precipitates, which are detrimental to the properties. Preferably, the S content is at most 0.01%, better still at most 0.005%. Achieving a very low S content, i.e. less than 0.0001%, is very costly and unprofitable. Therefore, the S content is generally at least 0.0001%.

[0074] Preferably, the phosphorus content is at most 0.05%, more preferably at most 0.02%. Achieving a very low P content, i.e. less than 0.0001%, is very expensive, so the P content is generally at least 0.0001%.

[0075] The steel may be subjected to a calcium sulfide globularization treatment, which has the effect of improving the bending angle due to the globularization of MnS. Therefore, the steel composition may contain at least 0.0001% Ca and at most 0.005% Ca.

[0076] The balance of the steel composition is iron and impurities resulting from the processing, which as detailed above may include up to 0.25% Cu, up to 0.05% Sn, up to 0.03% As, up to 0.03% Sb and / or up to 0.03% Pb.

[0077] The composition of the steel may be selected depending on the desired mechanical properties, particularly with regard to strength and ductility.

[0078] In particular, if a tensile strength in the range of 950 to 1200 MPa is desired together with a bending angle higher than 75 ° (measured according to the VDA 238-100 bending standard of July 2020), then in the entire part or at least in one region of the part, the steel of the steel substrate or at least one region of the steel substrate preferably comprises, in weight %, 0.062%≦C≦0.095% 1.4%≦Mn≦1.9% 0.2%≦Si≦0.5% 0.020%≦Al≦0.070% 0.02%≦Cr≦0.1% 1.5%≦(C+Mn+Si+Cr)≦2.7% 0.0035%≦Ti≦0.072% 0.0002%≦B≦0.004% 0.04%≦Nb≦0.06% 0.044%≦(Nb+Ti)≦0.09% 0.001%≦N≦0.009% 0.0005%≦S≦0.003% 0.0001%≦P≦0.020% Ca≦0.005%, and the remainder of the composition consists of iron and unavoidable impurities resulting from processing.

[0079] On the other hand, if a tensile strength of at least 1400 MPa is required, the steel of the steel substrate or at least a region of the steel substrate preferably comprises, in weight percent: 0.15%≦C≦0.30% 0.5%≦Mn≦3.0% 0.10%≦Si≦0.50% 0.005%≦Al≦0.1% 0.01%≦Cr≦1.0% 0.001%≦Ti≦0.2% 0.0002%≦B≦0.010% 0.0005%≦N≦0.010% 0.0001%≦S≦0.05% 0.0001%≦P≦0.1% Ca≦0.005% The remainder of the composition consists of Fe and unavoidable impurities resulting from processing.

[0080] If an even higher tensile strength of 1800 MPa or more is required, the composition of the steel substrate or at least a region of the steel substrate preferably comprises, in weight percent: 0.3%≦C≦0.4% 0.5%≦Mn≦1.0% 0.40%≦Si≦0.80% 0.01%≦Al≦0.1% 0.1%≦Cr≦1.0% 0.008%≦Ti≦0.03% 0.0005%≦B≦0.003% Ni≦0.5% 0.01%≦Nb≦0.1% 0.1%≦Mo≦0.5% N≦0.005% 0.0001%≦S≦0.004% 0.0001%≦P≦0.02% Ca≦0.0010% According to a third preferred composition comprising:

[0081] The steel substrate of a hot stamped coated steel part typically has a microstructure consisting of, by volume fraction, at least 60% martensite, up to 20% bainite, up to 5% ferrite, and up to 15% austenite.

[0082] The martensite fraction can be as high as 100%, and the bainite, ferrite and austenite fractions can be as low as 0% each.

[0083] This microstructural description applies to the majority of the steel substrate, meaning that this microstructure is present in at least 95% of the volume of the steel substrate, and preferably the entire volume of the steel substrate.

[0084] The microstructure is determined by the following method: Test pieces are cut from the hot stamped coated steel parts, polished as detailed below and etched with Nital 2% (10 s) to reveal the microstructure. The cross sections are then examined with an optical microscope at a magnification of ×500 and, if it is necessary to distinguish between martensite and bainite, with a scanning electron microscope (SEM) (backscattered electron mode, magnification ×500, EHT (electron high voltage)=15.00 kV, scale 10 micrometers). The determination of the volume fractions of the individual components (martensite, bainite, ferrite, austenite) is carried out by image analysis in a manner known per se.

[0085] In one embodiment, the austenite fraction is at most 5% by volume and / or the bainite fraction is at most 10% by volume.

[0086] In one embodiment, the microstructure consists, by volume, of at least 80% martensite, at most 10% bainite, at most 5% austenite, and at most 5% ferrite.

[0087] In a preferred embodiment, the microstructure is essentially martensitic, ie, consisting, by volume, of at least 95% martensite and at most 5% bainite and / or ferrite.

[0088] More preferably, the microstructure is fully martensitic.

[0089] The hot stamped coated steel part comprises an undeformed portion and at least one deformed portion.

[0090] In one embodiment, the hot stamped coated steel part includes two or more non-deformed portions.

[0091] Indeed, during stamping, particularly hot stamping, to produce a part, one or more portions of the blank are not deformed, while other portions are deformed to reach the final non-flat geometric shape of the part. The or each non-deformed portion is not deformed during hot stamping, and may not have been deformed during a previous cold pre-deformation of the blank, if one is performed.

[0092] Not deformed means that during the stamping process, the non-deformed part has an equivalent deformation of up to 0.01.

number

number

number

number

[0093] For example, the main deformations of a given molded part

number

number

[0094] In cases where the above methods cannot be applied, for example because only a portion of the complete molded part is available, or to assess the deformation very locally in certain areas, for example at the edges, Electron Backscatter Diffraction (EBSD) measurements combined with Scanning Electron Microscopy (SEM) observations can be performed. This relies on the correlation that exists between the deformation and the local crystallographic misorientation. For example, the following reference gives an example of such measurements: "Kamaya M. Assessment of local deformation using EBSD: quantification of accuracy of measurement and definition of local gradient. Ultramicroscopy. 2011 Jul;111(8):1189-99. doi:10.1016 / j.ultramic.2011.02.004. Epub 2011 Feb 21. PMID:21763236".

[0095] Another methodology that can be applied to determine the predominant deformation of a formed part is to measure the thickness of the deformed material in the formed area and compare it to the thickness of the non-deformed area.

[0096] The or each non-deformed portion is a flat portion of the part.

[0097] The or each non-deformed portion is for example a flange of a part or a flat portion located between two deformed portions of a part. As an example, for a hat-shaped part, the flat portion may further include the flat top of the hat-shaped stamped part.

[0098] An example of such a component is shown diagrammatically in FIG.

[0099] Figure 1 shows a hot stamped coated steel part 1 welded to a flat part 2 by a number of spot welds 3. The spot welds 3 are located in this example at a flange 8 of the hot stamped coated steel part 1.

[0100] The exemplary hot stamped coated steel part 1 is a hat-shaped part (or "omega" shaped part) with a flat top 4, two first curved portions 5 (or radii) extending from two opposing longitudinal edges of the flat top 4, two side walls 6 each extending from the longitudinal edges of the first curved portions 6, two second curved portions 7 each extending outwardly from the longitudinal edges of the side walls 6, and two flat flanges 8 each extending from the longitudinal edges of the second curved portions 7 to the outer edges of the part 1. The flanges 8 thus form the edges of the part 1.

[0101] In this example, the flange 8 and flat top 4 are flat, non-deformed parts of the hot stamped coated steel part 1 .

[0102] The non-deformed parts can be distinguished from the deformed parts in their shape and / or by observing cracks in the coating of these parts.

[0103] In fact, as will be described in more detail below, the coating on the deformed portion contains wide cracks that are absent or nearly absent in the coating on the non-deformed portion.

[0104] Each undeformed portion is not deformed but is subjected to the same thermal cycle as the deformed portion.

[0105] The hot stamped coated steel part of the present invention differs from a flat blank produced by austenitizing and quenching without deformation not only in that it includes at least one deformed portion resulting from hot stamping, but also in that the entire hot stamped coated steel part is subjected to a thermal cycle due to hot stamping that is different from the thermal cycle experienced by a non-deformed steel sheet.

[0106] In particular, each non-deformed portion is not deformed but experiences the same thermal cycles as the deformed portions in hot stamping during heating, transfer to the die and retention within the die.

[0107] Thus, in a hot stamped coated steel part, the or each deformed portion is deformed during hot stamping and the or each undeformed portion is not deformed but is subjected to the same thermal cycle as the deformed portion during hot stamping.

[0108] The hot stamped coated steel parts of the present invention obtained by the in-die hot stamping process are also different from samples produced by heating in a laboratory furnace or a technique without any surface contact, such as a Gleeble machine, which are uniaxially deformed in said furnace. In fact, such samples do not have undeformed parts and are subjected to a uniaxial deformation (tensile deformation), whereas in hot stamping the deformation is not uniform throughout the part but is three-dimensional. Moreover, the thermal cycles that the hot stamped coated steel parts undergo are different from those that are subjected to in a laboratory furnace, which does not involve transfer or stamping in a die.

[0109] The or each flat non-deformed portion of the part shall have a uniform thickness e of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm. pflat It is a part having the following structure.

[0110] For example, flanges with different thicknesses e pflat(1) and e pflat(2) When the region consists of two regions having the following structure, each of these regions is a separate non-deformed portion.

[0111] If the hot stamped coated steel part has a uniform thickness, the thickness of the flat non-deformed part (or each non-deformed part) is the thickness of the hot stamped coated steel part e P is equal to.

[0112] If the hot stamped coated steel part has a variable thickness and contains two or more non-deformed parts, the thickness of the non-deformed parts is e Pflat(i) where i=1...n is an index associated with each non-deformed portion, n is the number of non-deformed portions, and the thicknesses of the non-deformed portions may be different from one another or may be the same.

[0113] Thickness e pflat can be measured, for example, with a micrometer.

[0114] Hot stamped coated steel parts comprise a coating on at least a surface of a steel substrate.

[0115] The coating is an aluminum alloy coating.

[0116] The coating contains aluminum and iron, and preferably also contains silicon.

[0117] The coating advantageously contains more than 50% aluminium.

[0118] For example, the coating contains 8-12 wt% Si and 3-5 wt% Fe, with the balance being Al and unavoidable impurities.

[0119] The coating results from interdiffusion between the aluminum alloy pre-coating and the steel during hot stamping.

[0120] The coating comprises an interdiffusion layer located at the innermost part of the coating, i.e. in contact with the steel substrate.

[0121] The interdiffusion layer generally has an Fe content of at least 80%, and up to 95%, and an Al content of 4% to 20%, with up to 2% Si.

[0122] In one embodiment, the interdiffusion layer has a composition of 86-95% Fe, 4-12% Al, and 0-2% Si.

[0123] The coating further comprises an outer layer extending from the diffusion layer to the surface of the coating.

[0124] The outer layer generally contains or consists of an intermetallic compound of Fe, Al, and optionally Si.

[0125] The outer layer may be composed of a single layer or may itself be composed of sublayers of different intermetallic compounds.

[0126] For example, the outer layer may consist of 1 to 4 sublayers.

[0127] However, in the present invention, the inventors have found that whatever the layers in the coating, in particular whatever their composition and number, the object of the invention is achieved if the linear density of the cracks complies with the conditions defined below.

[0128] In the hot stamped coated steel parts according to the invention, the total thickness of the coating e coating and the thickness of the interdiffusion layer e IDL satisfies the following conditions: 40≦E pc <=80 In

number

[0129] E pc If the value of E is less than 40, the coating may not adequately protect the part for the intended application and good paint adhesion and spot weldability may not be guaranteed.pc If the value exceeds 80, the coating may become brittle and generate dust.

[0130] In the hot stamped coated steel part according to the invention, the coating has a hardness of 40≦E in at least one non-deformed part of the hot stamped coated steel part. pc The coating is applied to the non-deformed part with a thickness e ≦80. pflat Depending on the minimum linear density of cracks, dC min (e pflat ) or more, and is defined as follows:

number

[0131] In this formula,

number

[0132] Here, the "linear crack density", referring to the number of cracks per millimeter, is of course not a volume density, but a linear density in that it measures the number of cracks present in a cross section of the coating over a given length in a direction parallel to the surface of the steel substrate.

[0133] Indeed, the inventors have conducted intensive research to solve the problem of increasing spot weldability and paint adhesion and have surprisingly discovered that, contrary to the established belief that cracks are detrimental to the properties of hot stamped coated steel parts, both spot weldability and paint adhesion increase dramatically when the linear density of cracks exceeds a threshold value.

[0134] The inventors have also discovered that the relevant parts of the part in terms of linear density of cracks are non-deformed parts that, despite being subjected to the same thermal cycle as the deformed parts, did not undergo deformation because they were located on a flange of the hot stamped part or in a flat area between two deformed parts of the part (e.g. the flat top of a hat shaped part as shown in FIG. 1 ).

[0135] Indeed, in the deformed parts, the coating undergoes deformation during stamping, which leads to cracks in the coating due to the difference in expansion between the substrate and the coating, and depending on the temperature of deformation at each location and the applied deformation rate. However, the inventors have found that having a large number of cracks in some deformed parts is not enough to guarantee good spot weldability and good paint adhesion, at least in that it does not guarantee such properties in other parts of the hot stamped coated steel part.

[0136] Preferably, the non-deformed portion is located within the flange of the part, which is the area most likely to be spot welded, so it is especially desirable to have good spot weldability (as well as good paint adhesion) in this area.

[0137] The inventors have further discovered that the threshold linear density of cracks is not an absolute value, but rather depends on the thickness of the undeformed portion, with a higher linear density of cracks being required as the thickness of the undeformed portion decreases to achieve the desired spot weldability and paint adhesion.

[0138] As a result of these investigations, the inventors have determined that the coating of the parts is 40≦E pc If ≦80, the linear density of cracks in the coating in the non-deformed part is dC min It has been found that excellent spot weldability and paint adhesion are achieved when the above mentioned values ​​are met.

[0139] Preferably, the linear density of cracks in the coating is at most 4 * dC min , preferably at most 3 * dCmin It remains as it is.

[0140] Preferably, the hot stamped coated steel part comprises two or more non-deformed parts, and the linear density of cracks in each non-deformed part dC(i) is determined by the thickness e of this non-deformed part. pflat Related to (i):

number

[0141] Therefore, each undeformed part has a thickness of 0.6 mm to 3.5 mm e pflat (i), where i=1...n is an index associated with one of the non-deformed portions, and n>2 is the number of non-deformed portions, and the thickness e pflat The linear density of cracks in the coating in each non-deformed part of (i), dC(i), is

number

number

number

[0142] This formula is valid whether the non-deformed portions are all the same thickness or of different thicknesses.

[0143] The cracks in the coating extend from the surface of the coating in a direction substantially perpendicular to the surface of the steel substrate (i.e., the interface between the steel substrate and the coating) to a depth of at least 5 μm. The cracks have a width (parallel to the surface of the steel substrate) of less than 2 μm.

[0144] Thus, cracks are distinct from possible gaps in the coating having a width greater than 2 μm, cracks in deformations that may also have a width greater than 2 μm, and voids or coating defects that affect the coating over a depth of less than 5 μm.

[0145] Moreover, as mentioned above, in the non-deformed part, the cracks generally have a width of up to 1 μm. In particular, the average width of the largest crack, which is a crack having a width larger than the width of 90% of the cracks in the coating, is less than 1 μm. In other words, the average width of the 10% of the cracks having the largest width among the observed cracks is less than 1 μm. The average here refers to the average calculated from the widths of all the largest cracks.

[0146] In contrast, in the deformed portion, the coating comprises more cracks having a width greater than 1 μm, and may be as large as 2 μm or even 3 μm, such that the average width of the cracks is generally greater than 1 μm. In either case, the or each deformed portion has an average width of cracks greater than 1 μm, with the cracks having a width greater than the width of 90% of the cracks.

[0147] Preferably, the coating of the non-deformed portions does not have gaps or cracks having a width of 2 μm or more.

[0148] The linear density of cracks is determined as the ratio of the number of cracks observed in a cross-section of an undeformed part under a bright-field optical microscope over a total observation length of at least 5 mm (in a direction parallel to the surface of the steel substrate) to this total length (i.e. the number of cracks divided by the total length).

[0149] In particular, the linear density of cracks in the coating is determined by observing the cross-section of the coating of two samples taken from the non-deformed portion of the hot stamped coated steel part under a bright field microscope at 500x magnification over multiple fields of view, with the total length of the field (parallel to the surface of the steel substrate) being at least 5 mm. The linear density of cracks is then determined as the ratio of the number of observed cracks to the total length of the field of view.

[0150] In fact, the inventors have determined that to ensure the desired good spot weldability and good paint adhesion, at least dC over a small portion of the coating is required. min They further found that to achieve these properties, it is necessary to have a linear density of cracks of at least dC measured over a length of at least 5 mm. min It has been found that it is necessary to have a linear density of cracks of

[0151] The average width of the largest crack is determined by measuring the width of all cracks observed over the length of observation, identifying the largest cracks from these measurements, and calculating the average value of the widths of these largest cracks.

[0152] In particular, the characteristics of the above-mentioned coatings are determined as follows.

[0153] First, a sample is taken from the part and prepared.

[0154] For that purpose, in the non-deformed part of the hot-stamped coated steel part, a suitable size specimen of 20×30 mm is prepared by cutting the part in the middle of its length.

[0155] The cutting step is carried out carefully using a hard iron cut-off wheel (e.g. Struers 60A25) or, preferably, a micro-cutting device to avoid excessive stress that may damage the sample.

[0156] The samples are then cleaned (preferably in an ultrasonic bath) and dried with ethanol and compressed air.

[0157] The sample is then cold mounted with resin. Cold mounting is chosen instead of hot mounting because the gap between the resin and the sample is very small or non-existent. This is important because the gap can be the source of several preparation problems such as etching problems, scratches, or coating damage. The resin is preferably liquid EpoFix® resin mixed with Epofix Hardener®. Polymerization lasts for 10 hours. Two protective metal sheets (guard plates) are provided on either side of the sample to protect the coating from surface damage during polishing. Each time, two samples are mounted together to ensure that these two samples are subjected to the same polishing.

[0158] The sample is then carefully polished. The polishing step is a critical step in assessing the characteristics of the coating, since incorrectly performed polishing will result in defects in the coating. These defects include adhesion of diamond particles, damage to the coating such as coating delamination, and more importantly cracks in the coating, especially longitudinal cracks. Longitudinal cracks running in a direction approximately parallel to the surface of the steel substrate may reflect preparation problems and must be avoided during polishing to ensure reliable results when counting the number of cracks.

[0159] Polishing is divided into three main stages: disk polishing, die-grinding and oxide polishing. The sample must be washed and dried after each polishing step to remove polishing contamination and checked under an optical microscope.

[0160] First, the specimen is polished with an abrasive disk SiC paper P320 for 120 seconds using a specimen holder rotation speed of 150 RPM (revolutions per minute) and a disk rotation speed of 100 RPM, rotating in the same direction. A force of 15 N is applied and the specimen is washed with water.

[0161] Next, a 9 μm diamond polish is used to remove material from the surface without introducing scratches or deformation. This step is important to ensure the flatness of the polished surface. The rotation speed is the same as in the previous step, but the sample rotation is opposite to the disk rotation. This stage is set for 300 s and uses a force of 20 N. The polishing disk is damped with lubricant in an optimal amount (0.5 mL / 30 s) to ensure better material removal. The sample is washed with water.

[0162] The final step is oxide polishing with colloidal silica solution (1 mL / 5 sec). This step lasts for 90 sec with a sample holder rotation speed of 150 RPM and a disk rotation speed of 60 RPM, rotating in the same direction. The applied force is 20 N. The samples are first washed with water and then with ethanol.

[0163] The specimens are then etched with nital (2%, for 5-10 seconds) to reveal the steel microstructure and the steel / coating interface.

[0164] Total coating thickness e coating and the thickness of the interdiffusion layer e IDL To determine, the sample is imaged using a scanning electron microscope (SEM) (backscattered electron mode, magnification 500x, preferably WD (working distance) of 10 mm, EHT (electron high voltage) = 15.00 kV, scale 10 micrometers) to show a cross section of at least a portion of the coating as well as the base steel.

[0165] From the image, the interdiffusion layer can be identified as the light layer closest to the steel substrate.

[0166] The total thickness of the coating (including the interdiffusion layer) and the thickness of the interdiffusion layer are measured at five spots spaced horizontally by 15 μm.

[0167] The total thickness of the coating and the thickness of the interdiffusion layer are then calculated as the average of the obtained values. Thus, the total thickness of the coating e coating and the thickness of the interdiffusion layer eIDL is the average thickness.

[0168] In addition, the composition of the interdiffusion layer can be determined as follows.

[0169] The samples are viewed under a scanning electron microscope (SEM) to show a cross section of the coating as well as at least a portion of the base steel.

[0170] By energy dispersive spectroscopy (EDS), the composition is determined at 10 spots, considering two vertically spaced spots in the interdiffusion layer at five different horizontal locations.

[0171] The composition of the interdiffusion layer is then calculated as the average of the obtained values.

[0172] If desired, the composition of the entire coating can be measured by EDS.

[0173] The determination of the linear density of cracks in the coating of the non-deformed parts is carried out as follows.

[0174] Two samples mounted in the same resin were imaged under a bright field optical microscope (500x magnification) showing a cross section of the coating as well as at least a portion of the steel substrate at multiple locations on the sample.

[0175] Next, for each sample, 10 separate, non-overlapping fields are randomly selected and observed, each field having a length (parallel to the surface of the steel substrate) of at least 250 μm.

[0176] Therefore, the total length of observation, which is the total length of the field of view of the two samples (parallel to the surface of the steel substrate), should be 5 mm or more (>250 μm * 2 * 10).

[0177] In each field, it is first checked whether there are any longitudinal cracks running in a direction approximately parallel to the surface of the steel substrate. If longitudinal cracks are present, the field is ignored and replaced, since the presence of such cracks means that the sample preparation (cutting, polishing) was incorrectly performed at this location.

[0178] Cracks are then identified in each field that run from the top surface of the coating towards the steel substrate, generally perpendicular to the surface of the steel substrate.

[0179] To distinguish cracks from possible gaps in the coating, only cracks having a width less than 2 μm are identified as cracks. A 2 μm wide crack can be readily identified at 500x magnification, but if desired, the width of the crack can be measured as detailed below. Furthermore, to distinguish the cracks from voids or coating defects, the length of the crack is measured and only cracks having a depth of at least 5 μm (in a direction approximately perpendicular to the surface of the steel substrate) are considered as cracks.

[0180] The number of cracks is counted in each field and the total number of cracks in the 20 fields observed is calculated.

[0181] The linear density of cracks in the coating is then determined as the ratio of the total number of cracks to the total length of the field of view of the two samples.

[0182] Determining the average width of the largest crack, or more generally the width of any crack, can be done as follows.

[0183] The cross sections used to evaluate the linear density of cracks are observed under a bright-field microscope at 500x magnification, using a camera with a resolution of 3072 x 2048 pixels, and the images are displayed such that one pixel on the camera appears as one pixel on the image. The magnification at the time of imaging is 3020x.

[0184] The width of each of the cracks in all fields is determined.

[0185] To do so, for each crack, the width is measured at three locations located at the center of the crack and at a distance of 2 μm on either side of the center. The average of the three widths is determined as the width of the crack.

[0186] Then, the cracks that are larger than the maximum width, i.e., the width of 90% of the cracks in the coating, are identified. These cracks are therefore 10% of the cracks with the maximum width. The average width of these cracks is then calculated as the sum of their individual widths divided by their number.

[0187] If the number of cracks is such that 90% of the number of cracks is not an integer, the 90% result by number of cracks is rounded to the nearest integer (e.g., 90% of 108 cracks is considered to be 97 cracks, and 90% of 135 cracks is considered to be 122 cracks).

[0188] The hot stamped coated steel parts according to the invention have, at least in the non-deformed parts, a weld range of more than 1 kA, measured according to standard SEP 1220-2 (2011).

[0189] The hot stamped coated steel parts further have excellent paint adhesion in that, at least in the non-deformed parts, when subjected to dry paint adhesion and wet paint adhesion tests according to standard ISO 2409:2013, the dry paint adhesion is strictly less than 1 and the wet paint adhesion is equal to or less than 1.

[0190] Next, a method for producing a hot stamped coated steel part according to the present invention is disclosed.

[0191] The method includes providing a steel blank having an average thickness generally between 0.6 mm and 3.5 mm, preferably between 0.7 mm and 3.0 mm. This thickness is generally equal to the average thickness e of the hot stamped coated steel part that is to be produced from the blank. P is the same as:

[0192] The blank has on at least one surface an aluminum or aluminum alloy pre-coating, the pre-coating having an average thickness in the range of 19.91 μm to 40 μm.

[0193] Preferably, the blank has on each of its two main faces an aluminium or aluminium alloy pre-coating, the pre-coating having an average thickness in the range 19.91 μm to 40 μm.

[0194] This pre-coating can be aluminum or an aluminum alloy (containing more than 50% aluminum).

[0195] Advantageously, the pre-coating is an aluminium-silicon alloy containing by weight 7% to 15% silicon, 2% to 4% iron and optionally 0.0015% to 0.0030% calcium, the remainder being aluminium and unavoidable impurities resulting from processing.

[0196] Preferably, the pre-coating contains, by weight, 8% to 11% Si, 2% to 4% Fe, optionally 0.0015% to 0.0030% Ca, the balance being Al and impurities resulting from smelting.

[0197] The pre-coating is generally obtained by hot-dip plating in an Al or Al alloy bath.

[0198] In one embodiment, the blank is a monolithic blank, i.e. a blank consisting of a single sub-blank obtained by cutting a pre-coated steel sheet.

[0199] A monolithic blank is, for example, a tailor rolled blank, i.e. a blank with variable thickness obtained by differential rolling during the steel sheet manufacturing process.

[0200] In another embodiment, the blank is a tailor welded blank produced by assembling, in particular welding together, for example by laser welding, a number of blanks cut from different pre-coated steel sheets, known as sub-blanks.

[0201] In one embodiment, the blank has a uniform thickness of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm.

[0202] In another embodiment, the blank is a tailor rolled blank or a tailor welded blank, and the blank has a variable thickness.

[0203] In this case, the blanks are each made of different thicknesses e of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm. Bi It consists of two or more regions with a given thickness e Bi Each area of ​​the blank having a thickness of the final hot stamped coated steel part e Pi This corresponds to the area.

[0204] In either case, the blank is cut to a uniform thickness e that is determined to be the non-deformed portion of the hot stamped coated steel part after the hot stamping process. Bflat The flat portion has a thickness e Bflat Also, the thickness is 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm.

[0205] In other words, the thickness e Bflat is the thickness of the portion of the blank that is converted into the corresponding undeformed portion of the hot stamped coated steel part during hot stamping.

[0206] Blank part thickness e Bflat is the thickness of the corresponding undeformed part of the part e pflat is equal to.

[0207] In one embodiment, the blank comprises two or more non-deformed portions of the hot stamped coated steel part, each having a uniform thickness e Bflat(i) (i=1...n, where n is the number of such parts).

[0208] Each thickness e Bflat(i) is in the range of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3.0 mm. Bflat(i) is the thickness of the corresponding undeformed part of the part e Pflat(i) is equal to.

[0209] If the blank thickness is uniform, the thickness e Bflat , or each thickness e, if applicable Bflat(i) is the thickness of the blank e B is equal to.

[0210] The blank, or each sub-blank if the blank is a tailor welded blank, is preferably made of a steel having a composition disclosed above, in particular according to the first, second or third preferred compositions. The sub-blanks may be of the same steel composition or of different steel compositions.

[0211] The blank or each sub-blank is produced, for example, as follows.

[0212] Semi-finished products in the form of slabs, thin slabs or / and ingots, which can be further hot rolled, are preferably provided with the above mentioned steel compositions. The thickness of said semi-finished products is typically in the range of 50-250 mm.

[0213] If necessary, this semi-finished product is heated to a temperature generally in the range of 1100°C to 1300°C and then hot rolled, preferably at a finish rolling temperature in the range of 880°C to 950°C, to obtain a hot rolled steel sheet. The hot rolled steel sheet is coiled at a temperature Tc of not more than 750°C, generally not less than the temperature Ms of the steel.

[0214] At this stage, the thickness of the hot rolled steel sheet may be in the typical range of 1.5-4 mm. Depending on the thickness of the hot rolled steel sheet and the desired thickness of the sheet, the sheet may be pickled in normal conditions and further cold rolled, or directly annealed in the process described below.

[0215] If the blank produced is a tailor-rolled blank, the steel sheet can be produced by differential rolling (or continuous flexible rolling), i.e. by a process in which the sheet thickness obtained after rolling is variable in the rolling direction, related to the load applied to the sheet through the rollers during the rolling process.

[0216] After hot or cold rolling, in preparation for coating, the sheet is typically annealed at a temperature comprised between Ac1 and Ac3, generally in the range 700-850°C, to recrystallize the grains if cold rolling has been performed. The sheet is then hot-dip galvanized in an Al or Al alloy bath, generally at a temperature of about 670-680°C (the exact temperature depends on the bath composition).

[0217] The preferred pre-coating is Al-Si, obtained by hot-dipping the sheet in a bath containing, by weight, 7%-15% Si, 2%-4% Fe, optionally 0.0015%-0.0030% Ca, the balance being Al and impurities resulting from smelting.

[0218] Preferably the bath contains, by weight, 8% to 11% Si, 2% to 4% Fe, optionally 0.0015% to 0.0030% Ca, the balance being Al and impurities resulting from smelting.

[0219] The precoated steel sheet is then cooled to room temperature.

[0220] The pre-coated steel sheet is cut to obtain blanks (or sub-blanks), the geometry of which is related to the final geometry of the hot stamped coated steel part.

[0221] If the blank from which the part is manufactured is a tailor welded blank, the sub-blanks manufactured as described above are welded together.

[0222] In one embodiment, the sub-blanks have the same composition. In another embodiment, the compositions of the sub-blanks are different. This is especially true when different mechanical properties are required in different locations of the final part. As an example, the composition of the steel in the first sub-blank is selected from among the three preferred compositions listed above, and the composition of the second sub-blank is selected from among two other preferred compositions, or within the same preferred composition as the first sub-blank, but with a different specific composition.

[0223] In one embodiment, the sub-blanks have the same uniform thickness. In another embodiment, the sub-blanks have different thicknesses.

[0224] Optionally, before the heating in the mold and the hot stamping step, the blank can be cold formed to obtain a pre-deformed blank. This cold pre-deformation allows a smaller amount of deformation in the subsequent hot stamping step. In any case, the part of the blank that is destined to become the non-deformed part of the hot stamped coated steel part after the hot stamping process is not deformed during such cold pre-deformation. This part of the blank therefore remains flat. On the other hand, the part of the blank that is then subjected to deformation in hot stamping is only partially deformed during cold pre-deformation. As a result, it is guaranteed that the cold pre-deformation does not affect the targeted coating properties.

[0225] The blank (flat or cold pre-deformed) is then heated in a furnace at a temperature T heat is heated to

[0226] Heating is performed until the temperature of the blank reaches the melting temperature T melt a first heating stage in which the temperature of the blank is maintained below the melting temperature T melt The thermal temperature T heatand a second heating stage at which the temperature is increased to

[0227] The heating means is not limited and can be radiative, conductive, inductive, or resistive based.

[0228] The time spent by the blank during each of these two stages can be adjusted by controlling the furnace, in particular by using a furnace with different sections, each with independent settings, for example with respect to power and temperature, so that in each of these sections the heating rate can be adjusted independently of each other. For example, if a high heating rate is desired in the first heating stage, the first section of the furnace can be set to a high temperature and high power to ensure such rapid heating. The final heating temperature T heat If a low heating rate is desired, the melting temperature T melt To ensure a longer time above the melting temperature T of the precoating, multiple sections may be used and the furnace temperature may be increased slightly between sections. Conversely, melt and heating temperature T heat If a shorter heating time is desired, a high temperature can be set in the furnace section so that the blank will reach the target heating temperature T before reaching this temperature. heat can be transferred to the section.

[0229] Additionally, one skilled in the art knows how to determine the melting temperature of a pre-coating, the composition of which is known, using, for example, a ternary phase diagram.

[0230] The heated blank is then heated to a heating temperature T heat is held in

[0231] Preferably, the total residence time in the furnace, including heating and holding, is in the range of 1.5 minutes to 15 minutes.

[0232] The heated blank is then transferred to a mold (or hot stamping press) for a transfer time of preferably up to 15 seconds, more preferably up to 10 seconds or up to 8 seconds.

[0233] The die is then closed to stamp the blank into a part, and the temperature of the blank when the die is closed is T close is recorded as.

[0234] Preferably, the elapsed time between the transfer of the heated blank to the mold and the closing of the mold is less than 8 seconds.

[0235] The heating and holding causes interdiffusion between the pre-coating and the steel substrate. In particular, during the heating and holding, iron diffuses from the steel substrate into the coating and aluminum diffuses from the coating into the steel substrate, which interdiffusion results in the formation of an interdiffused layer of the coating.

[0236] Additionally, depending on the composition of the precoating, one or more intermetallic phases may be produced by interdiffusion above the interdiffusion layer (and thus within the outer layer of the component) in the form of a solid solution.

[0237] According to the present invention, the heating, holding, transporting, closing the mold and cooling in the mold are carried out in a dC min In order to achieve a linear density of cracks in the coating of the non-deformed parts of the hot stamped steel parts equal to or greater than dC, the thickness of the flat part of the blank that is transformed into the non-deformed part during hot stamping is e Bflat is controlled as a function of

[0238] In particular, the inventors aim to obtain a desired linear density of cracks in the coating of the non-deformed part, i.e. dC min The relevant factor for achieving a linear density of cracks dC above is not the time spent in the furnace, but the temperature of the blank when the mold is closed T close Combined with the melting temperature T of the pre-coating in the hot stamping process, melt Time spent by blanks beyond t MIt was found that.

[0239] At this time t M is the heating in the second stage (T melt ), heating temperature T heat Retention time T heat , the transfer time, and the formed blank cools to a temperature T melt This includes the time spent by the blank in the die until it reaches

[0240] At this time t M Monitor the temperature of the blank during heating and measure T as detailed above. melt By adjusting the time spent above the heating temperature T heat Retention time at t heat By controlling the transfer to the mold and T melt The temperature can be determined and controlled during the hot stamping process by controlling the time spent by the blank during cooling in the mold to.

[0241] The present inventors have confirmed that at least dC min To obtain the linear density of cracks at temperature T close The melting temperature of the precoating T must be in the range of 720 to 820 °C. melt Time spent beyond t M is the thickness e of the flat part of the blank, which is determined to be the non-deformed part. Bflat and heating temperature T heat and the melting temperature of the pre-coating T melt The minimum time t depends on Mmin and maximum time t Mmax It was found that the range must be

[0242] Minimum time t Mmin and maximum time t Mmax is defined as follows:

number

number

[0243] In these equations, t Mmin and t Mmax is expressed in seconds, T heat indicates the heating temperature of the blank in °C, and T melt denotes the melting temperature of the precoating in °C, and e Bflat indicates the thickness in mm of the flat part of the blank that is not deformed during hot stamping and is therefore destined to be the undeformed part of the part.

[0244] In fact, the inventors have found that by satisfying these conditions, after hot stamping and cooling, the linear density of cracks in the coating of the non-deformed part is dC min It has now been found that such hot stamped coated steel parts can be achieved.

[0245] On the other hand, at time t M does not satisfy the above relationship and / or the temperature T close If the temperature is higher than 820°C and lower than 720°C, the linear density of cracks becomes insufficient, making it impossible to achieve both excellent spot weldability and excellent paint adhesion.

[0246] In particular, the minimum time t Mmin Below this, the linear density of the cracks is insufficient and neither the paint adhesion nor the spot weldability is satisfactory.

[0247] On the other hand, the maximum time t Mmax Above this temperature, the linear density of the cracks becomes insufficient, and although paint adhesion can be improved by increasing the time above the melting temperature, the spot weldability becomes too low.

[0248] Naturally,

number

number

number

number

[0249] In one embodiment, the uniform thickness e B The blank has a thickness e of the part of the blank that is determined to be the non-deformed part of the part. Bflat Therefore, t Mmin and t Mmax becomes:

number

number

[0250] If the blank has a variable thickness, preferably, depending on the required properties, the time t M is the thickness e Bi For additional parts / areas of the blank with time t Mmin (e Bi ) and time t Mmax (e Bi ) may be adjusted to be included between

[0251] In that case, t Mmin and t Mmax The value of is blank e Bi can be calculated for each of the parts considered as a function of the thickness of this part. Then, M is the calculated minimum time t Mmin and the calculated maximum time t MmaxThe minimum value of

number

[0252] t Mmin and t Mmax The value of is an increasing function of thickness, which can be simplified as:

number

[0253] In other words, the minimum linear density of cracks dC in two or more parts of a part manufactured from two or more parts of a blank having different thicknesses min If it is desired to ensure a linear density of cracks exceeding M is the minimum time t defined for the thickest part. Mmin and the maximum time t defined for the thinnest part Mmax The range is between .

[0254] Preferably, the hot stamping is performed to a thickness e, where i=1...n. Bflat (i) is performed to form a hot stamped coated steel part including two or more non-deformed portions by hot stamping a blank such that two or more portions having the same length are not deformed, for a time t M is the minimum time t required for the thickest part Mmin and the maximum time required for the thinnest part, t Mmax The range is between .

number

[0255] In that case, all considered flat parts of the blank corresponding to the non-deformed parts of the part are scaled with their actual thickness e Bflat(i) The minimum time t Mmin and maximum time t Mmax Time t in the range between M It is guaranteed to be manufactured in

[0256] More preferably, the blank has a minimum thickness e Bmin and maximum thickness e Bmax and time t M is the maximum thickness e Bmax The minimum time t required for Mmin and the minimum thickness e Bmin The maximum time t required for Mmax The range is between .

number

[0257] In that case, all areas of the blank will have a minimum time t Mmin and maximum time t Mmax Time t in the range between M It is guaranteed that the material will be hot stamped.

[0258] Preferably, the temperature T of the blank when the mold is closed close is at least 740°C.

[0259] In one embodiment, the temperature T close is a maximum of 800°C.

[0260] In particular, at temperatures below 800°C T close can be up to 4 * dC min This allows the linear density of the cracks to be achieved, reducing the risk of powdering.

[0261] The heated blank is hot stamped in a die and die hardened.

[0262] In hot stamping, as detailed above, one or more portions of the blank are not deformed and at least one portion is deformed by hot stamping.

[0263] The undeformed portion of the blank becomes the undeformed portion of the resulting hot stamped coated steel part from the process.

[0264] The portion of the blank that is deformed forms the deformed portion of the hot stamped coated steel part.

[0265] The mode and amount of deformation in the deforming portion will vary from place to place due to the geometry of the final part and the forming tool. For example, some areas may be expanding while other areas are constrained and deforming. Whatever the deformation mode outlined above, the equivalent deformation

number

number

number

number

number

[0266] In the non-deformed part, the equivalent deformation is at most 0.01.

[0267] The hot stamped blank is then held in a die to ensure adequate cooling rates and to avoid distortion of the part due to shrinkage and phase transformation.

[0268] The hot stamped blank is cooled mainly by conduction through heat transfer with the die. The die may include coolant circulation to increase the cooling rate, or heating cartridges to decrease the cooling rate. The cooling rate can therefore be adjusted by implementing such measures.

[0269] The hot stamped blank is cooled to a temperature below 400°C.

[0270] The cooling rate applied depends on the composition of the steel and the desired structural and mechanical properties.

[0271] temperature T heat The average cooling rate from 0° C. to 400° C. (including cooling during transfer and cooling in the mold) is generally at least 27° C. / s, preferably at least 50° C. / s, and usually less than 200° C. / s.

[0272] Preferably the blank is cooled in the mould from the temperature of the blank when the mould is closed to 400°C at an average cooling rate of at least 30°C / s, more preferably at least 50°C / s.

[0273] For example, if the steel has a composition according to the first preferred composition described above, the hot stamped blank is first cooled at a temperature range between 750 and 450 ° C with a first average cooling rate ranging between 40 and 360 ° C / s. In this range, the transformation from austenite to martensite and possibly bainite occurs. In a further step, the hot stamped blank is cooled at an average cooling rate of 15 to 150 ° C / s, which is slower than the first cooling rate, in a temperature range between 450 ° C and 250 ° C inclusive.

[0274] When the steel has a composition according to the second preferred composition, the hot stamped blank is preferably cooled in a die at an average cooling rate of at least 30°C / s to a temperature below 400°C from the furnace outlet in order to achieve a structure essentially consisting of martensite.

[0275] If the steel has a composition according to the third preferred composition, the hot stamped blank is preferably cooled in the die to obtain a structure consisting of martensite or consisting of martensite and bainite.

[0276] In either case, the hot stamped blank is cooled in the die to a temperature below 400° C. and then cooled to room temperature to obtain the hot stamped coated steel part.

[0277] Working Example Steels having compositions A, B, C and D according to Table 1, expressed in weight percent, are B The coating is provided in the form of a blank cut from a pre-coated steel sheet having a coating composition.

[0278] The blanks were precoated on both sides with an Al-Si precoating with a composition of 8%–11% Si, 2%–4% Fe, and the remainder being Al and impurities due to smelting. All precoatings were melted at a melting temperature T of 577 °C. melt had the following characteristics:

[0279] The pre-coating thickness was adjusted in each case to the range of 19.91 to 40 μm, and the pre-coating thickness was adjusted to the sheet thickness e B are reported in Table 2 below.

[0280] [Table 1]

[0281] The balance of the composition is iron and incidental impurities, including Cu, the contents of which are reported above.

[0282] These pre-coated steel sheets are cut into blanks.

[0283] The blank is then heated in a furnace at temperature T heat Heat at T heatThe mixture was then held at 0° C. for 8 seconds and then transferred into the mold within 8 seconds.

[0284] The blank was then hot stamped in a die to produce a part with a deformed portion and a flat, non-deformed portion. In both cases, the blank was heated to a temperature T close The mold was closed when the temperature was 750°C.

[0285] The hot stamped blank was then cooled in the die to a temperature below 400° C., then removed from the die and cooled to room temperature to obtain the hot stamped coated steel part.

[0286] Heating, holding, transporting and cooling in the mold are performed according to the pre-coating T for each steel composition. melt The melting temperature is exceeded at various times t M was adjusted to reach

[0287] For each example, the melting temperature T melt Time spent by blanks beyond t M is reported in Table 2, and the minimum time t Mmin and maximum time t Mmax The minimum time t Mmin and maximum time t Mmax is the thickness of the blank e B , calculated using the above formula, which is equal to the thickness of the part of the blank in which the non-deformed part occurs.

[0288] [Table 2]

[0289] The hot stamped blank was then cooled in the die to a temperature below 400° C. to obtain a hot stamped coated steel part having a martensitic structure.

[0290] Hot stamped coated steel parts are manufactured using the thickness of the blank from which they were made e B Uniform thickness e equal to P (and eP =e Pflat (So ​​that it becomes).

[0291] Samples were taken from the undeformed portion of each part and prepared as described above.

[0292] Total coating thickness e coating and the thickness of the interdiffusion layer e IDL was determined using the protocol disclosed above, as well as the linear density of cracks in the coating.

[0293] The linear density of cracks in the coating of the non-deformed parts was in each case determined by observing 10 fields of view for each of the two samples, the total length of observation for the two samples being 5.29 mm.

[0294] Measured total coating thickness e coating and the thickness of the interdiffusion layer e IDL From the E determined according to the above formula pc The values ​​are reported in Table 3 below.

[0295] The linear density of cracks dC is the minimum linear density of cracks dC min are also reported in Table 3.

[0296] The paint adhesion was evaluated for each part as follows:

[0297] Samples were taken from the non-deformed areas of each part.

[0298] The samples were first degreased and then washed with Gardoclean® 5176 and surfactants at 55°C for 6 minutes. Refining was performed with Gardolene® ZL6.

[0299] The phosphating step was achieved by immersing the samples in a bath containing a solution of Gardobond® R24 TA and additives at 50° C. for 3 minutes.

[0300] A 20 μm layer of e-coating was then deposited by immersing the sample in a bath containing an aqueous solution of Pigment Paste® W9712-N6 and Resin blend® W7911-N6 from PPG Industries and applying a nominal voltage with a 30 second voltage rise time for a total of 180 seconds at 30° C. The sample was then wiped and cured in an oven at 175° C. for 30 minutes.

[0301] Dry paint adhesion test was then performed on a first set of samples by cross-hatching the e-coating layer with a cutter (scratches at 1 mm intervals), peeling off the e-coating layer with an adhesive tape (460 N / m) and assessing the amount of e-coating removed with the naked eye according to ISO 2409:2013, where 0 means excellent, i.e. little or no paint was removed, and 5 means very poor, i.e. a large amount of paint (>65%) was removed.

[0302] A wet paint adhesion test was then performed on the second set of samples: the samples were immersed in a closed box containing pure water at a temperature of 50° C. for 10 days.

[0303] After immersion, the surface of the e-coating was cross-hatched with a cutter (scratches at 1 mm intervals), the e-coating was peeled off with adhesive tape (460 N / m) and the amount of e-coating removed was assessed by the naked eye according to ISO 2409:2013. Again, 0 means excellent, in other words, little or no paint was removed, and 5 means very poor, in other words, a large amount of paint (>65%) was removed.

[0304] Additionally, the spot weldability was evaluated by determining the weld area of ​​each specimen according to standard SEP 1220-2(2011).

[0305] For Examples 7-12, which had a thickness of 1.2 mm, the following parameters were used: -Electrode:F1-16-20-5.5 -Welding force: 4kN - Welding current: Medium frequency direct current - Welding time: 320ms per pulse -Holding time: 200ms

[0306] For Examples 1-6 with a thickness of 1.8 mm, the following parameters were used: -Electrode:F1-20-20-8 -Welding force: 5kN - Welding current: Medium frequency direct current - Welding time: 3 pulses of 200ms each (40ms pause) -Holding time: 300ms

[0307] The dry and wet paint adhesion and weld coverage thus evaluated are reported in Table 3.

[0308] [Table 3]

[0309] Referring to Tables 2 and 3, Examples 2, 5, 8 and 11 were produced using the method according to the present invention, and the linear density of cracks was the minimum linear density of cracks dC min That's all.

[0310] Figure 2 shows the coating of Example 2 in cross section, as seen in one of the fields observed to assess the linear density of the cracks. In this image, contrasted for illustrative purposes only, multiple cracks are observed extending from the surface of the coating towards the steel substrate.

[0311] Of course, as mentioned above, the linear density of cracks in Example 2 was not determined based on this single field of view, but rather 20 fields of view were observed to determine the linear density of cracks over a sufficient observation length to be dC min (i.e., 15.5 cracks / mm) or greater.

[0312] In the inventive examples, the cracks were observed to be distributed almost uniformly in the coating on the flat, non-deformed portions, which was not observed in the cases of Comparative Examples 1, 3, 4, 6, 7, 9, 10 and 12 described below.

[0313] As a result, these Examples 2, 5, 8 and 11 have excellent dry paint adhesion, in each case less than 1, actually 0, meaning that no or very little paint was removed during the test, excellent wet paint adhesion, up to 1, as well as excellent spot weldability, with a weld range greater than 1kA.

[0314] Thus, Examples 2, 5, 8 and 11 are min It has been demonstrated that hot stamped coated steel parts according to the present invention having a linear density of cracks equal to or greater than this achieve excellent paint adhesion and spot weldability.

[0315] In contrast, Examples 1, 4, 7 and 10 exceed the melting temperature of the precoating for too short a time t M As a result, these examples were manufactured at dC min An example of a cross-sectional view of the coating of a flat, non-deformed part of Example 1 is shown in FIG. 3. In this view, no cracks are present in the coating. As a result, Examples 1, 4, 7 and 10 have low coating adhesion, since the dry coating adhesion is always 1 and the wet coating adhesion is higher than 1 in all cases.

[0316] Examples 3, 6, 9 and 12 also min For Examples 3 and 6, even though the dry paint adhesion was excellent and the wet paint adhesion was also good, the spot weldability was significantly reduced compared to the parts according to the invention due to the long time spent above the melting temperature of the coating, and therefore these examples reach the objective of the invention.

[0317] Furthermore, Example 12 shows the minimum linear density of cracks dC to achieve this objective.min In particular, this example shows, in comparison with examples 2 and 5, that having a linear density of cracks of, for example, 15.5 / mm, as in example 12, is not sufficient when the part has a thickness of 1.2 mm, but in contrast makes it possible to achieve the target properties for a higher thickness of 1.8 mm, as in examples 2 and 5.

[0318] Thus, the embodiment shows that the non-deformed portion of the part has a coating of dC min It is confirmed that, if the crack linear density is equal to or greater than this value, excellent spot weldability and excellent paint adhesion are achieved at least in this portion.

[0319] Further, the embodiment is directed to a temperature T above the melting temperature of the coating. close It has been demonstrated that by adjusting the process such that the time spent by the blank and the crack width are properly controlled, it is possible to achieve a desired sufficient linear density of cracks and therefore the desired properties.

[0320] Steel parts manufactured according to the invention can therefore be advantageously used in the manufacture of chassis or body-in-white parts or suspension arms for automotive vehicles.

Claims

1. A hot stamped coated steel part comprising a steel substrate and an aluminum alloy coating on at least one surface of the steel substrate, the coating comprising an interdiffusion layer and an outer layer proceeding outwardly from the steel substrate, the coating having a total thickness e coating and the thickness of the interdiffusion layer e IDL is the following condition, 40≦E pc ≦80 In [0010] Fulfilling e IDL is the thickness of the interdiffusion layer in μm, e coating denotes the total coating thickness in μm, The hot stamped coated steel parts have a thickness of 0.6 mm to 3.5 mm e Pflat and at least one deformed portion, wherein the linear density dC of cracks in the coating in the non-deformed portion is a minimum linear density dC of cracks defined as follows: min (e Pflat ) and [0025] Wherein dC and dC min (e Pflat ) is expressed in number of cracks per mm, e pflat indicates the thickness of the non-deformed part in mm, Hot stamped coated steel parts.

2. The linear density of cracks in the coating in the non-deformed part, dC, is 4 * dC min (e Pflat 2. The hot stamped coated steel part of claim 1, wherein the thickness of the coated steel part is equal to or less than 1 mm.

3. Hot stamped coated steel parts have a uniform thickness e ranging from 0.6 mm to 3.5 mm. P 3. The hot stamped coated steel part according to claim 1 or 2, having

4. The hot stamped coated steel parts have a variable thickness, and the hot stamped coated steel parts have a discrete thickness e ranging from 0.6 to 3.5 mm. Pi The hot stamped coated steel part comprises two or more regions having an average thickness e in the range of 0.6 mm to 3.5 mm. P 3. The hot stamped coated steel part according to claim 1 or 2, having

5. The hot stamped coated steel parts each have a thickness of 0.6 mm to 3.5 mm. pflat (i), and the linear density of cracks in the coating in each of the non-deformed portions, dC(i), is min (e pflat (i)) or more, [0030] In the formula, e pflat (i) denotes the thickness in mm of the non-deformed part considered, i = 1...n, n >= 2, and dC(i) and dC min (e pflat (i)) are expressed in number of cracks per mm, respectively, for thickness e Pflat 3. The hot stamped coated steel part according to claim 1 or 2, exhibiting a linear density of cracks and a minimum linear density of cracks in the coating of the considered non-deformed part of (i).

6. 3. The hot stamped coated steel part of claim 1 or 2, wherein in cross section, the cracks in the coating of the non-deformed portions extend from a top surface of the coating towards the steel substrate in a direction generally perpendicular to the surface of the steel substrate for a depth of at least 5 μm, and each crack has a width in a direction generally parallel to the surface of the steel substrate of less than 2 μm.

7. 3. The hot stamped coated steel part according to claim 1 or 2, wherein the linear density of cracks is determined as the ratio of the total number of cracks observed in several cross sections of the non-deformed part with a bright field optical microscope over a total observation length of at least 5 mm in a direction parallel to the surface of the steel substrate to the total observation length.

8. 3. The hot stamped coated steel part according to claim 1 or 2, wherein the hot stamped coated steel part is a monolithic part or a hot stamped welded part consisting of at least two hot stamped coated sub-parts and at least one hot stamped weld joining the hot stamped coated sub-parts together.

9. 9. The hot stamped coated steel part of claim 8, wherein the hot stamped coated steel part or each hot stamped coated sub-part has a structure consisting of at least 60% martensite, at most 20% bainite, at most 5% ferrite and at most 15% austenite, by volume.

10. The steel in the hot stamped coated steel part or in each hot stamped coated subpart comprises, in weight percent: 0.062%≦C≦0.4% 0.4%≦Mn≦3.9% 0.10%≦Si≦1.5% 0.005%≦Al≦1.0% 0.001%≦Cr≦2.0% 0.001%≦Ti≦0.2% 0.0005%≦B≦0.010% Ni≦2% Nb≦0.1% Mo≦0.65% W≦0.30% N≦0.010% 0.0001%≦S≦0.05% 0.0001%≦P≦0.1% Ca≦0.005% and having a chemical composition comprising 9. The hot stamped coated steel part of claim 8, wherein the balance of the composition is iron and unavoidable impurities resulting from processing.

11. The steel in the hot stamped coated steel part or in at least one hot stamped coated sub-part comprises, in weight percent: 0.062%≦C≦0.095% 1.4%≦Mn≦1.9% 0.2%≦Si≦0.5% 0.020%≦Al≦0.070% 0.02%≦Cr≦0.1% 1.5%≦(C+Mn+Si+Cr)≦2.7% 0.0035%≦Ti≦0.072% 0.0002%≦B≦0.004% 0.04%≦Nb≦0.06% 0.044%≦(Nb+Ti)≦0.09% 0.001%≦N≦0.009% 0.0005%≦S≦0.003% 0.0001%≦P≦0.020% Ca≦0.005%, and having a chemical composition comprising 11. The hot stamped coated steel part of claim 10, wherein the balance of the composition is iron and unavoidable impurities resulting from processing.

12. The steel in the hot stamped coated steel part or in at least one hot stamped coated sub-part comprises, in weight percent: 0.15%≦C≦0.30% 0.5%≦Mn≦3.0% 0.10%≦Si≦0.50% 0.005%≦Al≦0.1% 0.01%≦Cr≦1.0% 0.001%≦Ti≦0.2% 0.0002%≦B≦0.010% 0.0005%≦N≦0.010% 0.0001%≦S≦0.05% 0.0001%≦P≦0.1% Ca≦0.005% and having a chemical composition comprising 11. The hot stamped coated steel part of claim 10, wherein the balance consists of Fe and unavoidable impurities resulting from processing.

13. The steel in the hot stamped coated steel part or in at least one hot stamped coated sub-part comprises, in weight percent: 0.3%≦C≦0.4% 0.5%≦Mn≦1.0% 0.40%≦Si≦0.80% 0.01%≦Al≦0.1% 0.1%≦Cr≦1.0% 0.008%≦Ti≦0.03% 0.0005%≦B≦0.003% Ni≦0.5% 0.01%≦Nb≦0.1% 0.1%≦Mo≦0.5% N≦0.005% 0.0001%≦S≦0.004% 0.0001%≦P≦0.02% Ca≦0.0010% and having a chemical composition comprising 11. The hot stamped coated steel part of claim 10, wherein the balance of the composition is iron and unavoidable impurities resulting from processing.

14. 1. A method for producing a hot stamped coated steel part, comprising the following successive steps: Average thickness e of 0.6 mm to 3.5 mm B providing a steel blank having a thickness of 19.91 μm to 40 μm, the steel blank being provided on at least one side with an aluminum or aluminum alloy pre-coating, the pre-coating having an average thickness comprised between 19.91 μm and 40 μm; In order to obtain a fully austenitic structure in the steel of the blank, the steel blank is heated in a furnace to a heating temperature T in the range of 850 ° C. to 970 ° C. heat The steel blank is heated to a heating temperature T heat and holding the - transferring the heated blank into a mould and then closing the mould; - Thickness e of 0.6mm to 3.5mm Bflat hot stamping the blank in a die such that a flat portion of the blank having the blank is not deformed and at least a portion of the blank is deformed by the hot stamping, thereby obtaining a hot stamped blank comprising a non-deformed portion and at least one deformed portion; - cooling the hot stamped blank to a temperature below 400°C to obtain a hot stamped coated steel part; Including, The temperature of the blank when the mold is closed, T close is in the range of 720°C to 820°C, and the melting temperature T melt Time spent by the blank beyond t M is the minimum time t Mmin and maximum time t Mmax and [0045] and [0050] In the formula, t Mmin and t Mmax is expressed in seconds, T heat indicates the heating temperature of the blank in ° C., T melt denotes the melting temperature of the pre-coating in ° C., eBflat denotes the thickness of the undeformed blank part in mm, method.

15. 15. The method of claim 14, wherein the pre-coating is an aluminium alloy pre-coating containing, by weight, 7% to 15% silicon, 2% to 4% iron, and optionally 0.0015% to 0.0030% calcium, the balance being aluminium and unavoidable impurities.

16. 16. The method of claim 15, wherein the pre-coating is an aluminium alloy pre-coating containing, by weight, 8% to 11% silicon, 2% to 4% iron, and optionally 0.0015% to 0.0030% calcium, the balance being aluminium and unavoidable impurities.

17. In the hot stamping of the blank in the mold, each of the blanks is cut to a thickness e of 0.6 mm to 3.5 mm. Bflat (i) Two or more flat portions of the blank are not deformed and the melting temperature T melt Time spent by blanks exceeding t M is the minimum time t required for the flat part with the highest thickness Mmin (Max (e Bflat(i) ) and the maximum time t required for the flat part with the lowest thickness Mmax (Min(e Bflat(i) 16. The method according to claim 14 or 15, wherein the method is included between

18. The blank is formed to a minimum thickness e during hot stamping of the blank in the die. Bmin From maximum thickness e Bmax and the melting temperature T melt The time the blank spends beyond t M is the maximum thickness e Bmax The minimum time t required for Mmin (e Bmax ) and minimum thickness e Bmin The maximum time t required for Mmax (e Bmin 16. The method of claim 14 or 15, wherein the range is between

19. 16. The method according to claim 14 or 15, wherein the steel blank is a monolithic blank, a tailor rolled blank or a tailor welded blank produced by welding together at least two sub-blanks.

20. The blank or each subblank is, in weight percent, 0.062%≦C≦0.4% 0.4%≦Mn≦3.9% 0.10%≦Si≦1.5% 0.005%≦Al≦1.0% 0.001%≦Cr≦2.0% 0.001%≦Ti≦0.2% 0.0005%≦B≦0.010% Ni≦2% Nb≦0.1% Mo≦0.65% W≦0.30% N≦0.010% 0.0001%≦S≦0.05% 0.0001%≦P≦0.1% Ca≦0.005% and having a chemical composition comprising 20. The method of claim 19, produced by cutting pre-coated steel sheet, the remainder of the composition being iron and unavoidable impurities resulting from processing.

21. The chemical composition of the blank or at least one sub-blank is, in weight percent: 0.062%≦C≦0.095% 1.4%≦Mn≦1.9% 0.2%≦Si≦0.5% 0.020%≦Al≦0.070% 0.02%≦Cr≦0.1% 1.5%≦(C+Mn+Si+Cr)≦2.7% 0.0035%≦Ti≦0.072% 0.0002%≦B≦0.004% 0.04%≦Nb≦0.06% 0.044%≦(Nb+Ti)≦0.09% 0.001%≦N≦0.009% 0.0005%≦S≦0.003% 0.0001%≦P≦0.020% Ca≦0.005%, Contains 21. The method of claim 20, wherein the balance of the composition consists of iron and inevitable impurities resulting from processing.

22. The chemical composition of the blank or at least one sub-blank is, in weight percent: 0.15%≦C≦0.30% 0.5%≦Mn≦3.0% 0.10%≦Si≦0.50% 0.005%≦Al≦0.1% 0.01%≦Cr≦1.0% 0.001%≦Ti≦0.2% 0.0002%≦B≦0.010% 0.0005%≦N≦0.010% 0.0001%≦S≦0.05% 0.0001%≦P≦0.1% Ca≦0.005% Contains 21. The method of claim 20, wherein the balance is Fe and unavoidable impurities resulting from processing.

23. The chemical composition of the blank or at least one sub-blank is, in weight percent: 0.3%≦C≦0.4% 0.5%≦Mn≦1.0% 0.40%≦Si≦0.80% 0.01%≦Al≦0.1% 0.1%≦Cr≦1.0% 0.008%≦Ti≦0.03% 0.0005%≦B≦0.003% Ni≦0.5% 0.01%≦Nb≦0.1% 0.1%≦Mo≦0.5% N≦0.005% 0.0001%≦S≦0.004% 0.0001%≦P≦0.02% Ca≦0.0010% Contains 21. The method of claim 20, wherein the balance of the composition consists of iron and inevitable impurities resulting from processing.

24. The steps of providing the blank or each sub-blank may comprise the following successive steps: - providing a steel semi-finished product, - optionally reheating the semi-finished product to a temperature between 1100°C and 1300°C; - hot rolling the semi-finished product to obtain a hot rolled steel sheet; Coiling the hot-rolled steel sheet at a coiling temperature of −750° C. or less; - optionally pickling the hot-rolled steel sheet; Optionally, cold rolling the hot-rolled steel sheet to obtain a cold-rolled steel sheet; - heating a hot-rolled or cold-rolled steel sheet to an annealing temperature between Ac1 and Ac3, hot-dip galvanizing the steel sheet in an Al or Al alloy bath at a temperature of -670°C to 680°C; - cooling the precoated steel sheet to room temperature; - cutting the pre-coated steel sheet to obtain blanks or sub-blanks; - optionally welding the sub-blanks together to produce a tailor-welded blank; 20. The method of claim 19, comprising:

25. 15. Use of a hot stamped coated steel part according to claim 1 or produced by the method according to claim 14 for the manufacture of a chassis or body-in-white part or a suspension arm for an automotive vehicle.

Citation Information

Patent Citations

  • Clad hot-rolled and cold-rolled steel sheet, presenting a very high resistance after thermal treatment

    FR2780984A1

  • Method for manufacturing a body featuring very high mechanical properties, forming by drawing from a rolled steel sheet, in particular hot rolled and coated sheet

    FR2807447A1

  • Coated steel strip, a method for manufacturing the coated steel strip, a method for using the coated steel strip, a pressed blank manufactured from the coated steel strip, a pressed product manufactured from the coated steel strip, and a product containing such a pressed product.

    JP2010508438A

  • Method for manufacturing hardened parts without lme problems

    JP2018527462A

  • Press hardening method

    JP2023500842A